123 Adjunctive Brexpiprazole in Patients With MDD and Symptoms of Anxiety: Results From Post-Hoc Analyses of Three Placebo-Controlled Studies. (15th June 2018) - Weiller, Emmanuelle; Nylander, Anna-Greta; Weiss, Catherine; Zhang, Peter; Hobart, Mary
Abstract: Study objectives: Symptoms of anxiety are prevalent in Major Depressive Disorder (MDD) and are associated with greater illness severity, suicidality, impaired functioning and poor response to antidepressant treatment (ADT). In MDD, anxiety symptoms can be assessed as 'anxious distress' (new DSM-5 specifier) or 'anxious depression' (score ≥7 on the HAM-D anxiety/somatization factor). Brexpiprazole is a serotonin–dopamine activity modulator that is a partial agonist at 5-HT1A and dopamine D2 receptors, and an antagonist at 5-HT2A and noradrenaline alpha1B/2C receptors – all at similar potency. Brexpiprazole is approved in the US for treatment ofschizophrenia, and as adjunctive treatment in MDD. The objective of this post-hoc analysis was to assess the efficacy of brexpiprazole as adjunct to ADT in patients with MDDand anxiety symptoms, using these two definitions of anxiety. Methods: Data were pooled from three randomized, double-blind, placebo-controlled studies with similar designs (Pyxis – NCT01360645; Polaris – NCT01360632; Sirius – NCT02196506). In each study, patients with MDD and an inadequate response to 1–3 ADTs received single-blind ADT for 8 weeks. Patients with inadequate response throughout this prospective phase were randomized to receive either ADT+brexpiprazole (2mg in Pyxis and Sirius; 1mg or 3 mg in Polaris) or ADT+placebo for 6 weeks. Proxies used to categorize patients as having 'anxious distress' included a score of ≥2 on the following symptoms at randomization: tension (MADRS item 3 score ≥3); restlessness (IDS item 24 score ≥2); concentration (MADRS item 6 score ≥3); or apprehension (HAM-D item 10 score ≥3). Scores on the items of the HAM-D anxiety/somatization factor at randomization (baseline) were used to identify patients with 'anxious depression'. Efficacy was assessed as the change in MADRS total score from baseline to Week 6. Statistical analysis used a Mixed Model Repeated Measure approach using pooled brexpiprazole doses. Results: After 8 weeks of prospective ADT monotherapy, 57.6% (n=797/1, 383) of patients met the criteria for anxious distress, and 48.5% (n=671/1, 383) for anxious depression. The mean MADRS total score was 29.0 for patients with anxious distress in the adjunctive brexpiprazole (n=462) group and 29.1 in the placebo (n=327) group; while those with anxious depression were 28.9 (brexpiprazole; n=384) and 28.6 (placebo; n=282). Compared to those receiving placebo, patients with both anxious distress and anxious depression who received adjunctive brexpiprazole showed a greater improvement in MADRS total score (LS mean difference -2.38, p=0.0001 and -1.68, p=0.012, respectively). These improvements, compared to placebo, were similar to those in patients who had not met the criteria for anxious distress (-1.40, p=0.023) or anxious depression (-2.17, p<0.001). Conclusion: Adjunctive brexpiprazole may be efficacious in reducing depressive symptoms both in patients with or without symptoms of anxiety. Funding Acknowledgements: The studies were funded by H. Lundbeck A/S and Otsuka Pharmaceutical Development & Commercialization, Inc.